Lower inflammatory markers in women with antenatal depression brings the M1/M2 balance into focus from a new direction. (June 2017) - Edvinsson, Åsa; Bränn, Emma; Hellgren, Charlotte; Freyhult, Eva; White, Richard; Kamali-Moghaddam, Masood; Olivier, Jocelien; Bergquist, Jonas; Boström, Adrian E.; Schiöth, Helgi B.; Skalkidou, Alkistis; Cunningham, Janet L.; et al.
Highlights: Women with antenatal depression or SSRI treatment have lower levels of a number of peripheral inflammatory markers than healthy pregnant controls. No difference in any of the inflammatory markers was observed between women with antenatal depression and those who were using SSRI. The inflammatory markers were negatively correlated with cortisone serum concentrations in controls, but not in the cases. Differential DNA methylation of was found for seven of these inflammatory markers in a validation cohort. Abstract: Background: Antenatal depression and use of serotonin reuptake inhibitors (SSRI) in pregnancy have both been associated with an increased risk of poor pregnancy outcomes, such as preterm birth and impaired fetal growth. While the underlying biological pathways for these complications are poorly understood, it has been hypothesized that inflammation may be a common physiological pathway. The aim of the present study was to assess peripheral inflammatory markers in healthy women, women with antenatal depression, and in women using SSRI during pregnancy. Methods: 160 healthy pregnant controls, 59 women with antenatal depression and 39 women on treatment with SSRIs were included. The relative levels of 92 inflammatory proteins were analyzed by proximity extension assay technology. Results: Overall, 23 of the inflammatory markers were significantly lower in women with antenatal depression and in women on treatment with SSRIs in comparison with the healthy controls. No difference in any of the inflammatory markers was observed between women with antenatal depression and those who were using SSRI. Top three inflammatory markers that were down-regulated in women with antenatal depression were TNF-related apoptosis-inducing ligand (TRAIL), p = 0.000001, macrophage colony-stimulating factor 1 (CSF-1), p = 0.000004, and fractalkine (CX3CL1), p = 0.000005. Corresponding inflammatory markers in SSRI users were CSF-1, p = 0.000011, vascular endothelial growth factor A (VEGF-A), p = 0.000016, and IL-15 receptor subunit alpha (IL-15RA), p = 0.000027. The inflammatory markers were negatively correlated with cortisone serum concentrations in controls, but not in the cases. Differential DNA methylation of was found for seven of these inflammatory markers in an independent epigenetics cohort. Conclusion: Women with antenatal depression or on SSRI treatment have lower levels of a number of peripheral inflammatory markers than healthy pregnant controls. Hypothetically, this could be due to dysregulated switch to the pro-M2 milieu that characterizes normal third trimester pregnancy. However, longitudinal blood sampling is needed to elucidate whether the presumably dysregulated M2 shift is driving the development of antenatal depression or is a result of the depression.